Representações de professores de inglês sobre o livro didático - Cichelero, Marli (2014)
This study, conducted in the area of Applied Linguistics, specifically related to English language learning and teaching and teacher education, aims to investigate the representations that English teachers reveal upon textbooks. In order to achieve this goal, this study is grounded on the theory of Social Representations based essentially on Moscovici (2012) and also on other authors that discuss the concept as Spink (1995), Jodelet (2001), Ramos e Lessa (2010), among others; studies related textbooks in the perspective of learning and teaching, based on Cunningsworth (1984), Lajolo (1996), Coracini (1999), Soares (1999), Graves (2000), Richards (2002) e Tomlinson (2011); and the concept of mediation according to Vygtosky (1934/1984), and authors that discuss this concept, as Cole and Scribner (1984), Lantolf e Appel (1996), Wertsch, Del Rio e Avarez (1998), Lantolf (2001), Cole (2003), Daniels (2003), among others. This research is conducted according to the methodological framework of case study by Stake (1998) and it was developed in eleven schools of the public school system in four cities of the interior of Mato Grosso. Fifteen English teachers from elementary and secondary schools participated in the research. The data gathering was done by administering an online questionnaire. Based upon the questionnaire answers, the data analysis was carried out according to the Content Analysis Model by Bardin (2011). The results obtained revealed that the teachers representations point out the class textbook is an auxiliary tool, and a material of support, and that it serves to provide for activities, texts and content. Other representations revealed that the textbook is also a reference for teachers who can look for resources in it to enrich their class or to adapt teaching approaches to the needs of their students; in this perspective the textbook can be an input for the teacher to create other possibilities of instruction. Among the advantages, it was shown that the textbook offers the learner contact with the idiom reinforcing the representation that the textbook is also known as a tool that provides for such a contact. Among the limitations, the use of a textbook as the only resource in class was pointed out as limiting the learning development. In addition to this limitation another one revealed was that the textbook does not meet students needs. It was concluded that the representations identified are important for teacher education mainly regarding the use of the textbook, pointing out to the urge of promoting work that encourage the adaptation of this tool with its effective use for the development of teaching alternatives mainly directed to the students learning